USDA Inspected Livestock Slaughter Facilities in Florida - Chad Carr; Larry Eubanks; Ryan Dijkhuis (EDIS)
AN203, a 3-page illustrated fact sheet by Chad Carr, Larry Eubanks, and Ryan Dijkhuis, provides a comprehensive list of USDA inspected meat animal slaughter facilities in Florida. Published by the UF Department of Animal Science, July 2008.